Chapter Introduzione - Graziani, Michela (Studi e saggi, 2021)
This miscellaneous volume aims to commemorate the Iberian and European celebrations about Magellan that started in 2019. Specifically, the volume commemorates: the person and the image of Magellan on earth (celebrating the 500 years of his circumnavigation of the Earth) and in the universe (remembering the two Magellanic clouds); the Eddington's journey and the Apollo XI flight to the moon, through many essays that investigate the concept of travel in its several attitudes (explorative, scientific, philosophical, introspective, literary) in Sciences and Humanities, from ancient to contemporary ages, in an intercultural perspective, following a thematic scheme and a cronological one as well, if it is possible.